Treatment of the interaction between polymers and liquids in terms of the linear free energies concept - Makitra, R.; Yevchuk, I.; Musiy, R. (Condensed Matter Physics, 2005)
The existing theories of interaction between polymers and liquids don’t reveal
satisfactory relation between liquid physico-chemical properties and
the degree of swelling of polymer in polymer-liquid system. We suggested
the linear sixparametric equation, which takes into account both liquid capability
of specific and nonspecific solvation and its cohesion energy and
molar volume. This equation appears to be fit for treating the data within the
processes such as: diffusion of liquids through the thin films, dissolution of
polymers, swelling and extraction of coals. Існуючі теорії взаємодії між полімерами і рідинами не дають
задовільного зв’язку між фізико-хімічними властивостями рідини
і ступенем набрякання полімеру в системі полімер-рідина. Ми
запропонували лінійне шестипараметрове рівняння, яке враховує як
здатність рідини до специфічної і неспецифічної сольватації, так і
енергію когезії і мольний об’єм. Це рівняння виявилось придатним
для узагальнення даних таких процесів, як: дифузія рідин через
тонкі плівки, розчинення полімерів, набрякання і екстракція вуглів.